Redescription of the Caucasian endemic Diamesa caucasica Kownacki et Kownacka (Diptera: Chironomidae: Diamesinae) - Makarchenko, Eugenyi A.; Semenchenko, Alexander A.; Palatov, Dmitry M. (Zootaxa, 2022)
Diamesa caucasica Kownacki et Kownacka was described from the watercourses of the Terek River basin flowing down from the high mountain glaciers of the Caucasus (alt. 2000–2700 m a.s.l.), namely from the Chkheri River (Ortsveri Glacier), the Suatisi River (Savitisi Glacier) and the Mnaisidon River (Mna Glacier) in Georgia (Kownacki & Kownacka 1973). So far, no other finds of this species have been recorded in the Caucasus and other mountainous regions of Europe. Apparently, D. caucasica is endemic to the Caucasus and its distribution probably does not go beyond the glacial streams of the Terek River basin. This assumption is confirmed by the finds of adult males of this species made by Dmitry Palatov in 2018–2022 in the rivers at an altitude 1402–1980 m a.s.l., originating in the Mostocete, Tanantsete, Skazsky and Tseysky glaciers of North Ossetia and which also belong to the Terek River basin.